Ghost poles in the nucleon propagator: Vertex corrections and form factors - Krein, G. [UNESP]; Nielsen, M.; Puff, R. D.; Wilets, L. (American Physical Society (APS), 1993)
Vertex corrections are taken into account in the Schwinger-Dyson equation for the nucleon propagator in a relativistic field theory of fermions and mesons. The usual Hartree-Fock approximation for the nucleon propagator is known to produce the appearance of complex (ghost) poles which violate basic theorems of quantum field theory. In a theory with vector mesons there are vertex corrections that produce a strongly damped vertex function in the ultraviolet. One set of such corrections is known as the Sudakov form factor in quantum electrodynamics. When the Sudakov form factor generated by massive neutral vector mesons is included in the Hartree-Fock approximation to the Schwinger-Dyson equation for the nucleon propagator, the ghost poles disappear and consistency with basic requirements of quantum field theory is recovered. © 1993 The American Physical Society.